Gamma radiation-induced synthesis of novel PVA/Ag/CaTiO3 nanocomposite film for flexible optoelectronics - M. I. A. Abdel Maksoud; Soraya Abdelhaleem; Eman K. Tawfik; A. S. Awed (Scientific Reports, 2023)
Abstract A flexible nanocomposite film based on polyvinyl alcohol (PVA), silver nanoparticles, and calcium titanate (CaTiO3) was synthesized using gamma radiation induced-reduction. Temperature-dependent structural, optical, DC electrical conductivity, electric modulus, and dielectric properties of PVA/Ag/CaTiO3 nanocomposite film were investigated. The XRD pattern proved the successful preparation of the nanocomposite film. Also, as the temperature increases, the average crystallite sizes of CaTiO3 and Ag nanoparticles decrease from 19.8 to 9.7 nm and 25 to 14.8 nm, respectively. Further, the optical band gap increased from 5.75 to 5.84 eV with increasing temperature. The thermal stability is improved, and the semiconductor behavior for PVA/Ag/CaTiO3 nanocomposite film is confirmed by thermal activation energy ΔE with values in the 0.11–0.8 eV range. Furthermore, the maximum barrier Wm value was found of 0.29 eV. PVA/Ag/CaTiO3 nanocomposite film exhibits a semicircular arc originating from the material’s grain boundary contributions for all temperatures. The optical, DC electrical conductivity, and dielectric properties of the PVA/Ag/CaTiO3 nanocomposite film can be suitable for flexible electronic devices such as electronic chips, optoelectronics, and energy storage applications.